Efficacy and Safety of CT-P13 as First- and Second-Line Treatment in Patients with Ankylosing Spondylitis - Uslu, Sadettin; Gulle, Semih; Sen, Gercek; Capar, Sedat; Senel, Soner; Dalkilic, Ediz; Sari, Ismail (Mdpi, 2024)
Background/Objectives: CT-P13 is a biosimilar version of infliximab, a monoclonal antibody. In individuals with ankylosing spondylitis (AS), CT-P13 has been shown to be effective and to have a well-tolerated safety profile. The aim of this study was to evaluate the long-term drug persistence, safety, and efficacy of infliximab biosimilar CT-P13 in patients with AS undergoing first-line (1st-line) and later (>= 2nd-line) treatment in clinical practice. Methods: We performed an observational cohort study that included AS patients based on the biological drug database in the TURKBIO Registry between 2014 and 2021. The patients were divided into two groups: those receiving CT-P13 as first-line treatment or as a switch (>= 2nd-line) from another TNF inhibitor (TNFi). Standard disease activity metrics were used to assess the effectiveness of CT-P13, and drug retention rates were investigated. Results: There were 179 AS patients using CT-P13 (47.4% male, mean age: 42.9 +/- 11.3 years). Of these patients, 123 (68.7%) were receiving CT-P13 as a first-line treatment. The mean length of treatment was 3.5 years. CT-P13 drug retention rates in the general patient population were 58.6% and 48.2% in the first-line and >= second-line treatment, respectively, after 3 years of follow-up. The most common reason for CT-P13 treatment discontinuation was lack of efficacy. The first-line CT-P13 group had statistically substantially higher ASAS20/40 response rates at three and six months. Nonetheless, both groups' response rates at one year were comparable. Conclusions: In this real-world data analysis, AS patients who were TNFi na & iuml;ve (1st-line) and subsequently treated (>= 2nd-line) with CT-P13 showed encouraging drug retention rates with acceptable long-term effectiveness and safety.
Keywords: Ankylosing spondylitis; biosimilar; CT-P13; infliximab; cohort; TURKBIO